2006
DOI: 10.1007/s00330-006-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

Therapy monitoring using dynamic MRI: Analysis of lung motion and intrathoracic tumor mobility before and after radiotherapy

Abstract: A frequent side effect after radiotherapy of lung tumors is a decrease of pulmonary function accompanied by dyspnea due to developing lung fibrosis. The aim of this study was to monitor lung motion as a correlate of pulmonary function and intrathoracic tumor mobility before and after radiotherapy (RT) using dynamic MRI (dMRI). Thirty-five patients with stage I non-small-cell lung carcinoma were examined using dMRI (trueFISP; three images/s). Tumors were divided into T1 and T2 tumors of the upper, middle and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This amount of data is comparable to the motion analysis of Plathow et al (24/35 tumors in the upper and mid lobes [31]). Our numerical data give exact safety margins in all the three main directions and in Fig.…”
Section: Discussionsupporting
confidence: 60%
“…This amount of data is comparable to the motion analysis of Plathow et al (24/35 tumors in the upper and mid lobes [31]). Our numerical data give exact safety margins in all the three main directions and in Fig.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, lung cancer and POC were only identified in approximately 42% of cases on bolus enhanced CT. In recent years, MR imaging has been more widely used on the chest [18,19] and has the advantage of being radiationfree. MR imaging, an alternative method for differentiating cancer and POC, is advantageous since it is a technique that does not generally require the use of a contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…In particular for patients presenting with lung cancer, dMRI is a fast and reliable method to estimate tumor motion and chest wall or mediastinal adhesion and invasion [6,7]. This information can be useful for surgery planning as well as high precision radiotherapy to protect the surrounding healthy lung tissue [14].…”
Section: Introductionmentioning
confidence: 99%